A Self‐Assembled Matrix System for Cell‐Bioengineering Applications in Different Dimensions, Scales, and Geometries. Issue 13 (8th February 2022) - Xu, Yong; Gaillez, Michelle Patino; Zheng, Kai; Voigt, Dagmar; Cui, Meiying; Kurth, Thomas; Xiao, Lingfei; Rothe, Rebecca; Hauser, Sandra; Lee, Pao‐Wan; Wieduwild, Robert; Lin, Weilin; et al.
Abstract: Stem cell bioengineering and therapy require different model systems and materials in different stages of development. If a chemically defined biomatrix system can fulfill most tasks, it can minimize the discrepancy among various setups. By screening biomaterials synthesized through a coacervation‐mediated self‐assembling mechanism, a biomatrix system optimal for 2D human mesenchymal stromal cell (hMSC) culture and osteogenesis is identified. Its utility for hMSC bioengineering is further demonstrated in coating porous bioactive glass scaffolds and nanoparticle synthesis for esiRNA delivery to knock down the SOX‐9 gene with high delivery efficiency. The self‐assembled injectable system is further utilized for 3D cell culture, segregated co‐culture of hMSC with human umbilical vein endothelial cells (HUVEC) as an angiogenesis model, and 3D bioprinting. Most interestingly, the coating of bioactive glass with the self‐assembled biomatrix not only supports the proliferation and osteogenesis of hMSC in the 3D scaffold but also induces the amorphous bioactive glass (BG) scaffold surface to form new apatite crystals resembling bone‐shaped plate structures. Thus, the self‐assembled biomatrix system can be utilized in various dimensions, scales, and geometries for many different bioengineering applications. Abstract : This work explores the utility of liquid–liquid phase separation and a self‐assembling biomatrix system for manufacturing biomaterials in different dimensions, scales, and geometries and identifying a material, which can be applied at many stages of cell bioengineering, including from material discovery to in vitro application in both 2D and 3D.